Swearing-in Ceremony for Gary Austin (Superior Court) and Herbert Levy (Municipal Court) - Watkins, Howard::::::::: (1988)
Judge Levy's sister-in-law Vicky Schroebel, Aunt Barbara Boro, Judge Herbert Levy holding his son Daniel Levy, and Dan Schroebel, father-in-law Barbara Boro is mother to Bob and Herbert Boro